The learning curve for minimally invasive Oxford phase 3 unicompartmental knee arthroplasty: cumulative summation test for learning curve (LC-CUSUM) - Zhang, Qidong (BioMed Central, 2014)
BACKGROUND: The minimally invasive Oxford unicompartmental knee arthroplasty (UKA) is a demanding procedure but has many advantages compared with total knee arthroplasty (TKA). The aim of this observational study was to investigate the learning curve of one experienced surgeon introducing minimally invasive Oxford phase 3 UKA into his routine clinical practice. METHODS: The first 50 consecutive cases of minimally invasive Oxford phase 3 UKA performed by one surgeon were evaluated to determine whether there was an association between outcomes and the cumulative number of cases performed, indicating the presence of learning curve. The cohort was divided into two groups: group A comprised the first 25 cases and group B cases 26–50. Duration of surgery, blood loss, Hospital for Special Surgery score, range of motion, complications, and the radiographical position of the implant were compared between the groups. The cumulative summation test for learning curve (LC-CUSUM) was then used to further analyze the learning curve. RESULTS: The mean age and follow-up were 64.4 years and 50.9 months, respectively. The duration of surgery and blood loss were significantly more favorable in group B. The length of incision gradually reduced from 9.7 ± 1.3 to 8.5 ± 1.1 cm. Failures were identified in nine patients (18%). Two revisions and two dislocations were encountered in group A; one revision was performed 4 years after surgery for a patient in group B because of a fracture. One case of lateral compartment osteoarthritis was identified in group A. Two patients in each group reported continuing unexplained pains. CUSUM analysis showed that failure rates diminished rapidly after 16 cases and reached an acceptable rate after 29 cases. CONCLUSIONS: Minimally invasive Oxford phase 3 UKA for anteromedial osteoarthritis is a demanding procedure, but satisfactory outcomes can be achieved after approximately 25 cases.